2016
DOI: 10.1002/eji.201545955
|View full text |Cite
|
Sign up to set email alerts
|

Key roles of autophagy in regulating T‐cell function

Abstract: In the past 10 years, autophagy has emerged as a crucial regulator of T-cell homeostasis, activation and differentiation. Through the ability to adjust the cell’s proteome in response to different stimuli, different forms of autophagy have been shown to control T-cell homeostasis and survival. Autophagic processes can also determine the magnitude of the T-cell response to TCR engagement, by regulating the cellular levels of specific signaling intermediates and modulating the metabolic output in activated T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 94 publications
1
64
0
1
Order By: Relevance
“…It allows the orderly degradation of surplus or dysfunctional cellular components . In T cells, it is considered as an important mechanism regulating levels of signaling proteins and modulating cellular metabolism . For example, autophagy deficiency upregulates the metabolic regulators mTORC1 and c‐Myc, and glycolysis, which contribute to defective Treg‐cell function .…”
Section: Introductionmentioning
confidence: 99%
“…It allows the orderly degradation of surplus or dysfunctional cellular components . In T cells, it is considered as an important mechanism regulating levels of signaling proteins and modulating cellular metabolism . For example, autophagy deficiency upregulates the metabolic regulators mTORC1 and c‐Myc, and glycolysis, which contribute to defective Treg‐cell function .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most of the effective drugs are immunosuppressants that shut down the entire immune system (reviewed in [39]). Interestingly, several studies demonstrated that autophagy (macroautophagy and CMA) are important for the differentiation and activation of lymphocytes [39,[111][112][113][114][115][116][117][118]. In accordance, autophagy dysregulation has been described in various autoimmune diseases and some of the current treatment suggestions include autophagy regulators [39].…”
Section: Autoimmune Diseasesmentioning
confidence: 91%
“…Au-delà de son rôle protecteur lors de stress énergétiques, l'autophagie est impliquée de manière décisive dans la régulation de l'immunité, en particulier dans le développement, l'éducation et l'homéostasie des lymphocytes [11] ainsi que lors de la présentation antigénique. Divers modèles murins d'invalidation conditionnelle sont venus étayer le rôle primordial de plusieurs gènes liés à l'autophagie dans la fonction des LT, les données générées dans les LB demeurant encore complexes à analyser à ce jour [12][13][14][15][16][17][18]. Différents gènes autophagiques arbitrent en effet la qualité des fonctions des thymocytes.…”
Section: Synthèse Revuesunclassified